Into a footnote: Unpaid care work and the Equality Budget in Scotland. Issue 3 (August 2017) - Azong, Jecynta Amboh; Wilińska, Monika
This article analyses the visibility of unpaid care work in Scotland by examining the (non-)development of discourse on unpaid care work in economic policy documents. Drawing on the problem approach to policy analysis, the article engages with the Equality Budget Statements (EBS) as policy documents that not only inform the government's spending plans but are foremost statements of values and norms pursued by the government. This critical reading reveals that certain discourses give different meanings to women's lives through the political significance of what remains unproblematized as part of the ensuing care discourse in Scotland. The developing discourse on economic policy and equality suggests that equality in Scotland is presupposed on labour market participation. This shrinks discourse on unpaid care work; the problem of unpaid care work is silenced, while the problem of women's access to employment is redefined to mean a problem of difference and costly childcare only. The way certain issues have or have not appeared in governmental documents is explanatory of the importance and relevance of unpaid care work to the political discourse.